Students’ Perceptions of the Role of Local Wisdom-Based Creative Writing in Generating Creative Products - Alvionita Damayanti; Maria Arina Luardini; Maida Norahmi; Roni Kurniawan (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
Creative writing plays a crucial role in developing students’ creativity and writing skills. However, many students still encounter difficulties in generating ideas and expressing them effectively due to the lack of culturally relevant and contextualized learning materials. This study aims to investigate the implementation of creative writing integrated with local wisdom in generating creative products and improving students’ writing skills. This study employed a qualitative approach using a phenomenological design to explore students’ experiences and perceptions. The participants consisted of 18 students who completed a questionnaire and five students who participated in semi-structured interviews selected through purposive sampling. All participants were students of the English Education Study Program at Universitas Palangka Raya, specifically from the batch of 2022 in Class A, who had participated in a creative writing course and produced writing products. Data were collected through questionnaires and interviews and analyzed using thematic analysis, with method triangulation applied to ensure the credibility and trustworthiness of the findings. The findings reveal that the integration of local wisdom provides meaningful and familiar contexts that support students in generating ideas, organizing their writing, and expressing their thoughts more authentically. In addition, students demonstrated positive perceptions, including increased confidence, emotional engagement, and satisfaction with their writing. Importantly, the study found that creative writing based on local wisdom not only enhances students’ creativity and writing skills but also enables them to produce creative writing products, such as short stories and culturally grounded texts, which reflect their personal experiences and cultural identity and have the potential to contribute to the preservation of local culture for future generations. However, several challenges were identified, including difficulties in language use, coherence, and cultural representation.